Structural Reactivation Model of Post-Viral Destinations: An Analysis of Competitive Advantage as a Mediator of Rainbow Village Resilience - Ahmad Mansur; Tonny Hendratono; Sugiarto Sugiarto (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
The phenomenon of tourist destinations experiencing a decline in popularity after a viral phase (post-viral stagnation) poses significant challenges to the sustainability of urban tourism. This study aims to test a structural model for destination reactivation in Kampung Pelangi, Semarang, focusing on the role of digital transformation in strengthening destination resilience through the mediation of competitive advantage. Using a quantitative approach, data were collected from 150 respondents and analyzed using Structural Equation Modeling (SEM-PLS). The results of the hypothesis testing indicate that digital transformation has a positive and significant influence on competitive advantage (β = 0.495; t = 5.820; p < 0.001) and destination resilience (β = 0.312; t = 3.450; p < 0.001). Furthermore, competitive advantage was found to have a strong impact on resilience (β = 0.542; t = 7.115; p < 0.001). A mediation test demonstrated that competitive advantage significantly mediated the relationship between digital transformation and resilience (β = 0.268; t = 4.890; p < 0.001). This model demonstrated a predictive power of 61.2% (R2 = 0.612) for destination resilience. This finding emphasizes that post-pandemic destination reactivation requires the integration of digital capabilities that can restore differentiation and unique value propositions to achieve long-term resilience.